Metabolic and Network Pharmacological Analyses of the Therapeutic Effect of Grona styracifolia on Calcium Oxalate-Induced Renal Injury - Chen, Wei; Si, Yachen; Cheng, Jin; Ding, Jiarong; Zhao, Hongxia; Liu, Wenrui; Lin, Qishan; Hou, Jiebin; Guo, Zhiyong (Frontiers in Pharmacology, 2021)
Desmodium styracifolium (Osbeck) Merr. (DS), a popular folk medicine, is clinically applied in the treatment of nephrolithiasis. In this study, a urinary metabolic analysis was performed in a mouse model of renal calcium oxalate (CaOx) crystal deposition to identify the differential metabolites for oxalate-induced renal injury and explore the therapeutic mechanisms of DS against nephrolithiasis. Twenty-four mice were randomly divided into the control, oxalate and DS-treated groups. A metabolomics approach based on ultra-high-performance liquid chromatography coupled with quadrupole-time-of-flight mass spectrometry (UHPLC-Q-TOF/MS) was used for the metabolic profiling analysis of the urine samples. In addition, network pharmacology analysis was performed with different databases. As a result, the protective effects of DS were verified by biochemical parameters and crystal deposition detection. Fifteen metabolites were identified as the differential metabolites of crystal-induced renal injury. Most of them were involved in amino acid and fatty acid metabolism. Thirteen metabolites among them showed a reversal trend following DS treatment. A component-target-metabolite network was further constructed and nine overlapping target proteins of DS and the differential metabolites were discovered. Among these proteins, the estrogen receptor 2 (ESR2) expression in renal tissues was demonstrated to be significantly down-regulated while the androgen receptor (AR) expression was obviously increased in the oxalate group than control, which was reversed by DS. In conclusion, DS exerts therapeutic effect by regulating multiple metabolic pathways and the expression of ESR and AR in oxalate-induced renal injury.